increasing the activity and learning outcomes of IPA material plant self- adjustment to the environment through contextual approach for grade v students sd negeri 2 gombang cawas klaten 2020/2021 academic year - Marini Marini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The objectives of this learning improvement action research are to (1) Increase the activity and learning outcomes of science learning material on plant self-adjustment to the environment through a contextual approach for fifth grade students of SD Negeri 2 Gombang. This Classroom Action Research was carried out in two cycles. The subjects of this research were fifth grade students of SD Negeri 2 Gombang totaling 17 students. The data collection techniques used were observation, tests, and documentation. Data analysis techniques in this study used data source triangulation and method triangulation. The analysis technique used is interactive data analysis which includes data reduction, data presentation, drawing conclusions or data verification. The result of this study is that the application of a contextual approach can improve learning activities and outcomes for students. In the pre-cycle, the average student score was 61.18 with 35.29% completeness. After the implementation of the action, cycle I showed an increase in student activity and learning outcomes, namely the average student score rose to 72.35 with a completeness of 64.71%. In cycle II, there was an increase in the average value of students' understanding of the concept of material peaking at 81.18 with a completeness of 82.35%.